INFLUENCE OF SOLID PARTICLE AND SOYBEAN OIL OF PICKERING EMULSION DICLOFENAC DIETHYLAMINE USING TAGUCHI METHOD - Hutami, Shabrina Nindya; Kuncahyo, Ilham; Sulaiman, TN Saifullah (Jurnal Kimia Riset, 2024)
Emulsions stabilized by solid particles are called Pickering emulsions, using diclofenac diethylamine for topical use. In this study, screening for the effect of the type of solid particles (bentonite 3%; Avicel RC-591 2.5%; and kaolin 15%) and soybean oil concentration (10%; 20%, and 30%) using the Taguchi orthogonal array method, with independent variables (type of solid particles and concentration of soybean oil, dependent variables (viscosity, pH, %EE, creaming index, globule size, and % cumulative penetration). The Pickering emulsion with Avicel RC-591 for solid particles produced a stable emulsion during 21 days of storage. Using the Taguchi orthogonal array method, the best formula based on the dependent variable is Formula 4 with physical test results at viscosity 566 cp, pH value 8.18, adsorption efficiency 55.70%, creaming index 100%, globule size 57.1 µm, cell diffusion Franz test at 120 minutes resulted in a cumulative penetration of 69.829%. The penetration power of Formula 4 is better than the emulsion with tween and span emulsifiers, which has a cumulative amount at 120 minutes of 12.609%. Therefore, Avicel RC-591 2.5% solid particles with 10% soybean oil concentration resulted in a stable Pickering emulsion and better penetration than emulsions with tween and span emulsifiers.